EKSPERIMENTASI PENERAPAN ANALISIS SWOT DALAM MERUMUSKAN STRATEGI "PEMASARAN" PROFESSIONAL PENDIDIK MELALUI MOTIVASI KERJA (JS (JURNAL SEKOLAH), 2019)
Abstract: Experimentation of the Application of SWOT Analysis in Formulating Professional Marketing Strategies for Educators Through Work Motivation. The application of the SWOT analysis that was experimented was aimed at knowing the image of educators as professional experts. The sample studied consisted of two populations, namely students who were already working (alumni) and active students (final semester). The data analysis technique used is descriptive analysis and hypothesis testing (comparative test). The results showed that there were 60% of alumni who worked as teachers or educators while the other 40% worked as company workers and other entrepreneurs. Based on the results of the work motivation questionnaire filled out by alumni there were 29.75% strongly agree; 47.50% agree; 5.75% doubtful (don't know); 15.75% disagree and 1.25% strongly disagree.Keywords: SWOT, "marketing", work motivation, ExperimentationAbstrak: Eksperimentasi Penerapan Analisis SWOT dalam Merumuskan Strategi "Pemasaran" Professional Pendidik Melalui Motivasi Kerja. Penerapan analisis SWOT yang dieksperimentasikan ini bertujuan untuk mengetahui gambaran pendidik sebagai tenaga ahli yang professional. Sampel yang diteliti terdiri atas dua populasi yaitu mahasiswa yang sudah bekerja (alumni) dan mahasiswa aktif (semester akhir). Teknik analisis data yang digunakan adalah analisis deskriptif dan pengujian hipotesis (uji komparatif). Hasil Penelitian menunjukkan bahwa terdapat 60 % alumni yang bekerja sebagai guru atau pendidik sedangkan 40% lainnya bekerja sebagai pekerja perusahaan dan wiraswasta lainnya. Berdasarkan hasil angket motivasi kerja yang diisi para alumni terdapat 29,75% sangat setuju; 47,50% setuju; 5,75% ragu-ragu (tidak tahu); 15,75% tidak setuju dan 1,25% sangat tidak setuju.Kata kunci : SWOT,œpemasaran, motivasi kerja, Eksperimentasi